المنهج النحوي عند البصريين - Yasmadi Yasmadi (AT-TA'LIM, 2015)
the aim of the study is to identify the Arabic grammar based on  Nahu. Formerly, Basrah scholars focused on their study to determine Nahu and Arabic grammar. Although they agreed with Kufah group that hadits and word sayings of Arabic people can become references to in determining syntactical structure (grammar) of Arabic language. Thus, they  provide strong requirement to those references. Meanwhile the scholars made qiyas  as ijma` as Nahu regulations.  Copyright © 2015 by Al-Ta'lim All right reserved